2018
DOI: 10.3390/machines6020024
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Thrust Force and Cutting Torque in Drilling Based on the Response Surface Methodology

Abstract: In this research, experimental studies were based on drilling with solid carbide tools and the material used was Al7075. The study primarily focused on investigating the effects of machining parameters (cutting speed, feed rate, diameter of the tool) on the thrust force (F z ) and the cutting torque (M z ) when drilling an Al7075 workpiece. The experimental data were analyzed using the response surface methodology (RSM) with an aim to identify the significant factors on the development of both the F z and M z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 17 publications
0
18
0
2
Order By: Relevance
“…İlerleme miktarı parametresindeki değişim ise neredeyse lineer çizgi görünümlü bir eğri oluşturmakta ve artan ilerleme miktarı doğrudan tepki kuvvetini artırmaktadır. Bu durum literatürde gerçekleştirilen çalışmalar ile paralellik göstermektedir [9][10]13]. Fener mili devri parametresinin artmasına bağlı olarak tepki kuvveti düşmektedir.…”
Section: Yüzey Yanıt Yöntemiunclassified
See 1 more Smart Citation
“…İlerleme miktarı parametresindeki değişim ise neredeyse lineer çizgi görünümlü bir eğri oluşturmakta ve artan ilerleme miktarı doğrudan tepki kuvvetini artırmaktadır. Bu durum literatürde gerçekleştirilen çalışmalar ile paralellik göstermektedir [9][10]13]. Fener mili devri parametresinin artmasına bağlı olarak tepki kuvveti düşmektedir.…”
Section: Yüzey Yanıt Yöntemiunclassified
“…YYY ile elde etmiş oldukları matematiksel modeller ve ANOVA bağlı olarak tepki kuvveti ve kesme torku üzerindeki işleme parametrelerinin etkisini ortaya koymuşlardır. Sonuç olarak tepki kuvveti ve kesme torku üzerinde matkap çapı ve ilerleme miktarı doğrudan etki ederken, kesme hızının önemli bir derecede etki etmediğini tespit etmişlerdir [10]. Raja ve ark., GFRP kompozit malzemesinin yüksek hızda delinmesi sonucunda meydana gelen tepki kuvveti ve delaminasyon (katman ayrılması) faktörünü YYY ile incelemişlerdir.…”
Section: Introductionunclassified
“…Yi et al observed that the micro-milling of Al-6061-T3 alloy decreased surface roughness with increasing cutting speed and increased with increasing feed. In addition, they found that good coherence was obtained between experimental and predicted results with the response surface method optimization (RSM) technique (Yi et al, 2015), Kyratsis et al studied the effect of independent variables on dependent variables in drilling of Al-7075 alloy with RSM optimization technique (Kyratsis et al, 2018). The results of this study showed that the feed rate parameter on thrust force and cutting torque is more effective than cutting speed and optimization and experimental results are compatible with each other, Dikshit et al reported that the roughness of the machined surface in milling of Al-2014-T6 alloy increased with increasing feed rate and cutting speed.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis using the Taguchi method and Analysis Of Variance (ANOVA) revealed the optimum parameters for reducing the burr height and surface roughness, and regression models created using RSM were proven to be adequate to describe the correlation between process parameters and process outcome. Sreenivasulu and Rao [8], Efkolidis et al [9], and Kyratsis et al [10] also employed the Taguchi method to determine the optimum levels of the process parameters for the minimization of thrust force and torque during drilling of aluminum alloys. After they performed experiments at various cutting speeds, feed rates, and various drill diameters and geometries, they determined the most significant parameters of the process and their optimum values.…”
Section: Introductionmentioning
confidence: 99%